2021
DOI: 10.1371/journal.pone.0245730
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of hypertension and prehypertension in Peru: Evidence from the Peruvian Demographic and Health Survey

Abstract: Background Peru is a Latin American country with a significant burden of hypertension that presents worrying rates of disparities in socioeconomic determinants. However, there is a lack of studies exploring the association between those determinants, hypertension and prehypertension in Peruvian population. Objective We aimed to assess the association betwgeen socioeconomic determinants, hypertension and prehypertension using a nationally representative survey of Peruvians. Methods We performed a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
2
9
1
1
Order By: Relevance
“…The prevalence of prehypertension in males was higher than in females. This finding is similar to that reported in studies conducted in China [15], Jamaica [35], Mongolia [36], Nepal [37], Israel [38], United States [39], Peru [17], and Taiwan [40], in which men had a higher prevalence of prehypertension compared to women. It is postulated that this difference may be attributed to biological mechanisms related to sex hormones, which have been evaluated in animal models and in humans [41].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prevalence of prehypertension in males was higher than in females. This finding is similar to that reported in studies conducted in China [15], Jamaica [35], Mongolia [36], Nepal [37], Israel [38], United States [39], Peru [17], and Taiwan [40], in which men had a higher prevalence of prehypertension compared to women. It is postulated that this difference may be attributed to biological mechanisms related to sex hormones, which have been evaluated in animal models and in humans [41].…”
Section: Discussionsupporting
confidence: 90%
“…In South American countries such as Argentina, Uruguay, and Chile, prehypertension affects 32.5% of the general population, with a higher prevalence in men compared to women (36.0% vs. 29.4%) [16]. In Peru, a pattern similar to that of these countries is observed, with prehypertension affecting more than 30% of the general population, and in terms of gender, the male population has a higher prevalence and probability of presenting this condition compared to women [17]. These differences in the prevalence of prehypertension according to sex may be influenced by cardiometabolic and behavioral risk factors that behave differently in men and women [18].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, the same meta-analysis study suggested farming to be inversely associated with hypertension [ 44 ]. Similarly, a study in Vietnam reported a lower prevalence of hypertension among farmers compared to traders, construction workers, and government employees [ 14 ]. In high-income countries, an inverse association of education [ 48 ], income [ 11 , 48 , 49 ], and being employed [ 48 , 50 ] with hypertension was reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, in LMIC, this association is complex. For instance, the prevalence of hypertension was higher among low SES groups in Brazil [ 12 , 13 ] and Peru [ 14 ], while greater among high SES groups in South Asian countries [ 14 18 ]. Studies from Nepal have also reported an elevated blood pressure among affluent individuals [ 19 ], whereas highly educated individuals [ 4 , 5 ] and men doing labor-intensive work had normal blood pressure.…”
Section: Introductionmentioning
confidence: 99%